Kwestia wiarygodności tekstowej Nowego Testamentu w polskiej apologetyce i teologii fundamentalnej. Rewizja argumentów „z lektury” i „z wrażliwości na zmiany” - Kogut, Adam (Warszawskie Studia Teologiczne, 2024)
Polish apologists and fundamental theologians argue for the textual reliability of the New Testament in various ways. Among their arguments are those ‘from reading’ (i.e. the argument that the New Testament texts were read in Christian worship gatherings from the very beginning and that this counteracted textual changes) and ‘from sensitivity to changes’ (i.e. the argument that Christians were extremely sensitive to textual changes from the very beginning). In the article, however, it is claimed that both arguments are presented by Polish apologists and fundamental theologians in an unconvincing manner, while in contemporary historical research one can find sources and insights that could make the same arguments much more convincing.